Effect of mass variation of material on continuous vertical type drying machines against drying time - S. Syahrul; D.F. Nansah; A. Mulyanto; M. Mirmanto (Universitas Mataram, 2020)
Post-harvest handling of grain before being ground or stored for a long time is drying or reducing water content. To dry the grain is more effective by using a mechanical dryer. In this study, grain drying was carried out using a continuous vertical dryer by varying the grain mass to determine the effect of grain mass variation on the grain drying time. Mass variations observed were 10 kg, 20 kg, 30 kg, 40 kg, 50 kg, 60 kg, with an air temperature of 50°C and an air velocity of 7 m/s. The result showed that the more grain mass the lower the drying rate. However, the drying time was longer, and the efficiency was higher. At the 10 kg, the fastest drying time was 75 minutes. Whereas at the 60 kg, the maximum drying time was 150 minutes. The highest efficiency of 8.78, occured at a mass of 60 kg and the lowest efficiencywas 1.6% occured at a mass of 10 kg.